Consideration on Hemicraniectomy - H. Stan; B. Suciu; Al. Iosif; Adriana Cocis (Romanian Neurosurgery, 2010)
Decompressive hemicraniectomy is a surgical technique used to relieve the increased intracranial pressure. The aim of the current paper is to present our surgical technique and experience used in performing hemicraniectomies, technique that we consider optimal for his purpose. Our experience consists in 17 operated cases and eleven patients (64.7%) were long term survivors.